Presence of microplastics in marine species of the Marine National Park las Baulas - Astorga-Perez, Angelica (2022)
The ingestion of microplastics has been reported in various marine species, however, the degree of contamination in the systems and the biota associated with them is little known. This study presents the results of the presence of microplastics in seven species of pelagic fish and one species of benthic crustacean, all high trophic level from Las Baulas Marine National Park. By chemical digestion and visual inspection, microplastics were extracted from the digestive system of 56 individuals. A total of 90 pieces were extracted from 89% of the fish (93% fibers) with 3.75 ± 1.70 (SD) microplastic / fish. A significantly lower quantity was obtained in crustaceans with a total of 58 pieces extracted from 76% of the individuals analyzed with 2.64 ± 1.36 (CF) microplastic / crab. A search for microplastics in muscle tissues was carried out using the histology technique and lesions were found in the muscle tissue of the fish, but the results were not attributable to MP, therefore, these data will not be delved into. This article reports the presence of these pollutants in marine species with a high trophic level on the Pacific coast of Costa Rica, which confirms the impact by plastics in the study area, reinforcing the need for an integral solid waste management system.